Improving heterologous protein secretion at aerobic conditions by activating hypoxia-induced genes in Saccharomyces cerevisiae - Liu, Lifang; Zhang, Y.; Liu, Z.; Petranovic, D.; Nielsen, J. (2015)
Oxygen is important for normal aerobic metabolism, as well as for protein production where it is needed for oxidative protein folding. However, several studies have reported that anaerobic conditions seem to be more favorable in terms of recombinant protein production. We were interested in increasing recombinant protein production under aerobic conditions so we focused on Rox1p regulation. Rox1p is a transcriptional regulator, which in oxidative conditions represses genes induced in hypoxia. We deleted ROX1 and studied the effects on the production of recombinant proteins in Saccharomyces cerevisiae. Intriguingly, we found a 100% increase in the recombinant fungal a-amylase yield, as well as productivity. Varied levels of improvements were also observed for the productions of the human insulin precursor and the yeast endogenous enzyme invertase. Based on the genome-wide transcriptional response, we specifically focused on the effect of UPC2 upregulation on protein production and suggested a possible mechanistic explanation.